The Sm-core mediates the retention of partially-assembled spliceosomal snRNPs in Cajal bodies until their full maturation. Issue 7 (5th February 2018) - Roithová, Adriana; Klimešová, Klára; Pánek, Josef; Will, Cindy L; Lührmann, Reinhard; Staněk, David; Girard, Cyrille
Abstract: Cajal bodies (CBs) are nuclear non-membrane bound organelles where small nuclear ribonucleoprotein particles (snRNPs) undergo their final maturation and quality control before they are released to the nucleoplasm. However, the molecular mechanism how immature snRNPs are targeted and retained in CBs has yet to be described. Here, we microinjected and expressed various snRNA deletion mutants as well as chimeric 7SK, Alu or bacterial SRP non-coding RNAs and provide evidence that Sm and SMN binding sites are necessary and sufficient for CB localization of snRNAs. We further show that Sm proteins, and specifically their GR-rich domains, are important for accumulating snRNPs in CBs. Accordingly, core snRNPs containing the Sm proteins, but not naked snRNAs, restore the formation of CBs after their depletion. Finally, we show that immature but not fully assembled snRNPs are able to induce CB formation and that microinjection of an excess of U2 snRNP-specific proteins, which promotes U2 snRNP maturation, chases U2 snRNA from CBs. We propose that the accessibility of the Sm ring represents the molecular basis for the quality control of the final maturation of snRNPs and the sequestration of immature particles in CBs.